Mellem kors og klasse: Kristelig dansk Fællesforbunds tilblivelse og første år 1899-1907 - Schädler Andersen, Lars (Arbejderhistorie - tidsskrift for historie, kultur og politik, 2013)
Lars Schädler Andersen: Between the cross and class, Arbejderhistorie 1/2013, pp. 34-52. The Christian Danish Confederation of Employers and Workers (KdF) was formed prior to the Great Lockout of 1899. In a European context the body was atypical with its corporative composition and an uncom-promising rejection of the right to strike. The Confederation was met with opposition from the social democratic trade union movement and only found a refuge on the periphery of the labour market. The internal debate within the KdF, however, reveals that to a large extent the limited adherence to the body can be explained by the fight of the Inner Mission (a very con-servative Lutheran movement in Denmark) to protect the ´true believers` within organisatio-nal forms which alienated the majority of wage labourers – Christian as well as the unbe-lievers. The defeat of the Christian Danish Confederation in the 1905 labour conflict in the textile industry gave rise to an internal debate between the “Opposition”, who wanted the development of a membership democracy and a more distinct trade union profile, and the “Conservatives”, who meant that the purity of faith was more important than building a strong membership base. In 1907 the conservative forces triumphed, securing the continued control of the leading organs of the Confede-ration by the Inner Mission at the expense of any potential progress in increasing member-ship.